STUDI GEOKIMIA DAN PEMODELAN KEMATANGAN BATUAN INDUK FORMASI TALANGAKAR PADA BLOK TUNGKAL, CEKUNGAN SUMATERA SELATAN - Susanto Sigit Wibowo; Eddy A. Subroto (Bulletin of Geology, 2017)
Talangakar Formation sediment, which is believed to be one of the major source rocks in South Sumatera Basin. Ditch cutting and oil samples were analyzed using geochemistry analysis and followed maturity modeling. The total organic carbon contents of the sediment range from 0.4–80% TOC and there are two types of source rocks which are shale and coals. The samples analyzed have vitrinite reflectance in the range of 0.2-0.65% Ro and Tmax value between 400-4500 C, which indicate that Talangakar sediments contain immature to late mature organic matter. The sediments are dominated by mixed type II/III and type III kerogen. Typical oil and gas generating potential is anticipated from the sediments with fairly high hydrogen indices (HI) from 50-400 mgHC/gTOC. One dimensional basin modeling was performed to analyze the hydrocarbon generation potential and expulsion history. The source rock of the Talangakar Formation at well location is presently at a stage of early to main oil generation, no gas generation with thermal maturity ranging from 0.5- 1.3% Ro. The modeled burial history suggests that maximum burial occurred in the Pliocene.